SOME TECHNOLOGICAL ASPECTS OF LAYING OF BRASS COVERING ON WIRE. PERFECTING OF THE COOPER PLATING TECHNOLOGY - A. A. Truhanovich; D. V. Gontarj; A. L. Aksenov (Литьë и металлургия)
The perspective of the original technology of cooper plating as one stage cooper plating using inert anodes of stainless steel is noted. Under certain conditions using of the electrolysis impulse regime becomes possible.